Financial Performance Of Sharia Commercial Banks In Indonesia: Does Capital Structure Matter? - Syarif, Ahmad; Maulana, Bisma; Salsabila, Zahro; Maulana, Angga (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2023)
Islamic banking has experienced a surge in financial growth in the last decade. Global economic challenges have encouraged many conventional banks to transform into sharia banks. Sharia banking can increase its operational efficiency by applying debt and equity financing methods by trade-off theory. This research investigates the effect of capital structure as measured by the debt-to-asset ratio (DAR) and debt-to-equity ratio (DER) on the financial performance of Sharia Commercial Banks as measured by return on assets (ROA) and return on equity (ROE). This research is quantitative with multiple linear regression analysis techniques. The data source comes from OJK Sharia Banking Statistics for 2017-2021. This study shows that DAR and DER have a significant effect on ROA. Apart from that, DAR has a substantial impact on ROE. However, this study indicates that DER does not significantly affect ROE.